Utilization of Digital Media Disruption as a Platform for the Development of Malay Culture for Medan City Youth - Abrar Adhani (International Journal of Economic, Technology and Social Sciences (Injects), 2023)
The presence of digital media is an important part that needs attention. The speed of information and communication that currently dominates society certainly also influences social and cultural life. The advancement of digital media has expanded to Indonesia, especially in urban areas. The development of digital media which is characterized by the expansion of internet networks in various countries with different cultures makes it easy for the people of one country or one city to another to share information, in various countries and cities. Digital media is a place for teenagers to introduce a culture that has begun to fade. This study aims to find out how much awareness the teenagers in Medan City have about local culture and how teenagers use digital media. This study used a qualitative descriptive research type by collecting data from journals for the last 10 years, other literature research and conducting interviews with Medan city youth. The result of this research is that teenagers are starting to be aware of the presence of local culture and redeveloping it by creating content through digital media platforms with the aim of introducing Malay culture to all corners of the world.